Viability and Sublethal Detection of Probiotic Bacteria on Instant Freeze-Dried Fermented Soy Milk (Study on Isolate Type and Sucrose Concentration as Cryoprotectant) - Nisa, Fithri Choirun; Wardani, Agustin Krisna; Chrisnasari, Ruth (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Fermented soy milk is one of probiotic beverage, contain high protein and isoflavon that ha healthy effect. However, the usage of soy milk as fermented product is not effective because needs low temperature. To overcome this problem is by converting the fermented soy milk into instant dried product. Â However, freeze drying can reduce the viability of probiotic. Â The aim of this research was to determine the isolate and sucrose concentration to obtain high viability of probiotic. This research was conducted in randomized block design with two factors. The first factor was type of isolate that consist of L. acidophilus, L. casei, and L. plantarum. The second factor was sucrose concentration (5% and 10%). Each treatment was done in four replications.The result showed significant difference of kind isolate treatment on reducing sugar, protein, total acid, pH, and total LAB during fermentation with total LAB and sub lethal on dried product, but no significant difference on total sugar and N-amino. Sucrose concentration treatment showed significant difference on total LAB, sub lethal, water content, and reserve ability water vapor, but no significant difference on solubility. Interaction of both treatments gave significant difference on total LAB and sub lethal. Â The best treatment resulted from the combination of 5% sucrose concentration and isolate L. acidophilus.Keywords: probiotic, cryoprotectant, freeze drying, instant fermented soy milk